Second Five Year Plan Progress Report 1959-60 Government of Rajasthan - Planning Commission (Planning Commission, 1959)
Rajasthan is an integral part of the Indian Republic and its economy could hardly be reviewed in isolation. The Indian economy during the year 1959-60 revealed mixed trends of sustained progress and stresses and strains of a developing plan. While there was improvement in the rate of growth of industrial output and the balance of payment position, the agricultural production declined and the prices continued to rise, though the rise as compared to the previous year was a little less during the year under review as compared to the rise in the preceding year over the year prior to that.
Directorate of Economics and Statistics, Government of Rajasthan